The Development of Learning Materials-Based Guided Narrative Writing Skills Writing in Elementary School - Lika Apreasta (International Journal of Educational Dynamics, 2019)
Abstract___ effected by the use of materials that are less able to attract students and writing less in accordance with the process of writing (pramenulis, saatmenulis, and pascamenulis). The goals achieved in the efforts of the development of these materials is to produce learning materials to write a narrative-based Guided Writing for teachers and students of class V SD a valid, practical, and effective. This type of research is research development. This research uses a 4-D model which consists of 4 stages: stage define, design, develop, and disseminate. Test the validity of the data obtained through the assessment of the response sheet teacher and students. The effectiveness of the activity seen from the students, assessment processes and results of narrative writing students. Based on the results of test validity, practicalities, and effectiveness of the materials obtained a valid, practical, and effective, as well as being able to enhance the narrative writing skills of students. It can be concluded that the materials to write a narrative using Guided Writing developed can be used in learning to write narratives in class V primary school.